Antioxidant Assay of the Ethanolic Extract of Three Species of Rattan Fruits using DPPH Method - Heriad Daud Salusu; Farida Aryani; Edy Budiarso; Irawan Wijaya Kusuma; Enos Tangke Arung; Abdul Rasyid Zarta (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
The bioactivity of some species of rattan fruit has been previously studied and it was found that it has potential antioxidant agents. This study was conducted to determine the antioxidant content in three species of edible rattan fruit, namely Calamus manan Miq., Calamus ornatus Bl. and Calamus caesius Bl by using the DPPH method, whereby the test was carried out on the pericarp, flesh, and seeds of each fruit. The research findings revealed that phytochemical compounds, i.e. flavonoids, tannins, and triterpenoids are found almost in all parts of the fruit, while steroid is not found in any of the three species of the fruit. The antioxidant activity found in the fruit of C. caesius Bl is strong, meanwhile the antioxidant activity in the fruit of C. manan Miq only strong in its pericarp and seeds, but it is moderate in its flesh. The antioxidant activity found in the fruit of C. ornatus Bl. is strong in its pericarp and seeds, but it is moderate in its flesh. Therefore, these three species of rattan fruit are potential as antioxidant agents.